2007
DOI: 10.1002/dneu.20521
|View full text |Cite
|
Sign up to set email alerts
|

Song and brain development in canaries raised under different conditions of acoustic and social isolation over two years

Abstract: Early isolation experiments indicate that male songbirds learn their songs during an early sensitive period, although later work has shown that some open-ended learners modify songs in later years. Recent isolation experiments suggest that in some species song has a stronger genetic basis than previously thought. This study raised domestic canaries under different combinations of acoustic and social isolation and followed song development into the second year. Males raised alone in acoustic isolation developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
3
24
1
Order By: Relevance
“…Their song differs from that of normally reared males in having a smaller repertoire size, a higher proportion of single syllables and a reduced repetition rate, similar to the study of Leitner & Catchpole (2007). A typical song of a tutor is shown in figure 1a.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Their song differs from that of normally reared males in having a smaller repertoire size, a higher proportion of single syllables and a reduced repetition rate, similar to the study of Leitner & Catchpole (2007). A typical song of a tutor is shown in figure 1a.…”
Section: Resultsmentioning
confidence: 88%
“…Second, although the presence of the tutors was crucial, the F 1 generation did not simply copy the 'abnormal' song model but developed rather species-typical song properties. A previous experiment on peer group male canaries, raised without an adult song model, had shown that these males adjust their song properties towards those of control males when exposed to conspecific tutors in their second year of life (Leitner & Catchpole 2007). Furthermore, they retained only approximately 20 per cent of their original syllables after transfer to the new environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations